Nandina domestica 'Harbor Dwarf' Harbor Dwarf Nandina: FPS422/FP422, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Nandina domestica ‘Harbor Dwarf’, commonly known as Harbor Dwarf Nandina. It describes the plant’s physical characteristics, including its compact size, dense foliage, and seasonal color changes. The document highlights the plant’s adaptability to various soil types and environmental conditions, such as its moderate drought tolerance and preference for full sun to partial shade. It also outlines the plant’s uses in landscaping, emphasizing its suitability for borders, mass plantings, and containers. Additionally, the document notes that Harbor Dwarf Nandina is an evergreen shrub that produces fewer fruits compared to other Nandina varieties. Original publication date October 1999.